Aplicação do método flash para a estimação da difusividade térmica da geléia de acerola - Silva, Mirtes Aparecida da Conceição (2011)
The analysis of the properties of heat and mass transfer in foods has been studied for many researchers due to their need for knowledge to feed the codes of optimization calculations and equipment design involving the addition and removal of energy. This work deals with the solution of an inverse problem of parameter estimation to estimate the thermal diffusivity and thermal conductivity of a sample of acerola jam. The direct problem is solved numerically using finite differences and the system of algebraic equations arising from the method is solved by explicit method. The experimental transient temperature profile required for the solution of the inverse problem is obtained by a thermal pulse method, specifically, via flash method. The experimental procedure consists of submitting a sample of acerola jelly confined in a cylindrical cavity with a thermal disturbance of short duration on one side (front) and measure the transient temperature evolution on the other side (back side). The acerola jelly was specially produced and analyzed physical and chemical for this purpose. For the thermal disturbance of the sample we used a device called a micro-flash, LFA model 457, manufactured by Netzsch. The pulse of short duration is from a power system that releases an energy equivalent to 15 joules per pulse and records the evolution of temperature using an infrared sensor, type ISB. This equipament has a system for generating laser pulse. The results are shown in terms of thermal diffusivity and thermal conductivity and are compared with the values available in literature for similar products. The values found for the thermal diffusivity of 0,121 to 0,148 mm2s-1 and the thermal conductivity of 0,372 to 0,497Wm-1 are in agreement with the values found by other techniques.